Fungal morphogenesis - Moore, David (Cambridge University Press, 1998)
Fungal Morphogenesis brings together in one book, for the first time, the full scope of fungal developmental biology. The book provides a coherent account of the subject and puts forward ideas that can provide the basis of future research. Throughout, the author blends together physiological, biochemical, structural and molecular descriptions within an evolutionary framework. Sufficient information is provided about fungal biology to give the reader a rounded view of the mycological context within which fungal morphogenesis is played out, without obscuring the broader biological significance.